METHODICAL TIPS FOR IMPROVING STUDENTS’ FOREIGN LANGUAGE SPEAKING SKILLS IN ENGLISH LESSONS - Lobachova, Iryna (Професіоналізм педагога: теоретичні й методичні аспекти, 2018)
The article is devoted to the problem of overcoming the language and speech barrier in communicative and cognitive situations aimed at development of students’ foreign language communicative competence. The main tasks of foreign language policy are studying English through the personal activity of learners; mastering professional vocabulary by students carrying out creative activity; teaching learners to speak English in relevant and understandable topics for them, which they can apply in real life situations; stimulating students to utterances; encouraging communication; creating an atmosphere of interest for each student in the group work; introducing both individual and group forms of work; using learning materials that promote rapid memorization of vocabulary, grammatical rules, etc. An important contribution to the study of the problem of motivation while teaching a foreign language is made by B. Ananiev, A. Lypkina, A. Markova, T. Matis, T. Kharchenko and others. The issue of using the innovative multimedia technology in studying English is considered by both native and foreign scholars: I. Zymnia, S. Nikolaieva, T. Pakhomova, Yu. Hapon, V. Liaudis, Ye. Nosenko and others. Such scientists, psychologists and teachers as V. Asieiev, J. Atkinson, Yu. Babanskyi, I. Bekh,I. Vasyliev, D. Elkonin, Yu. Kuliutkin, A. Leontiev, S. Rubinshtein, L. Slavina, H. Shchukina, P. Yakobson and others determine that the most important aspect of modern education is forming the motivation of studying. The analysis of literary sources indicates lack of comprehensiveness in the study of the mentioned problem and the need to investigate some aspects. The aim of the study is to find out the reasons which do not allow students to be participants in communicative situations and provide methodical tips on encouraging students to participate in subject discussions in English. In particular, the strategy of teaching foreign languages is determined by the needs of modern society and the level of development of linguistic, psychological and pedagogical sciences. This strategy is a communicative approach that determines the practical aim of learning foreign languages, namely: fluent mastering foreign languages, intercultural communication through the development of speaking skills. The reasons which do not allowed students to be full participants in a discussion (complicated issue, incomprehensibility of the proposed topic for discussion; inability to work in pairs or conversation groups; inability to select arguments for any statement, etc.) are outlined. Methodical recommendations for encouraging students to participate in communicative situations, subject discussions (emphasis on importance of the offered topic; possibility of creating their own structured utterances; forming their groups; ethics of communication; preparation for academic discussions; personal example; freedom of utterance; a right to make mistakes; principles of grouping students; favorable atmosphere, etc.) are given. Thus, the interactive technologies of teaching a foreign language create the necessary preconditions both for the development of students’ foreign language competence and the formation of skills to take collective and individual decisions. This is the basis for education of citizens with an active life position; it also activates language and speech material in students’ foreign language communication; stimulates their cognitive processes and develops professionally oriented skills in real life conversation situations.